Measurement of performance parameters and improvement in optimized solution of WEDM on a novel titanium hybrid composite - Bose, Soutrik; Nandi, Titas (Measurement : journal of the International Measurement Confederation, 2021)
Titanium matrix composite (TMC) is expansively used in different aerospace, biomedical and automobile industries due to its exceptional strength and resistant properties. This manuscript aims to provide the current state-of-art of enhancement of these tribo-mechanical properties by development of a novel TMC through laser engineering net shaping (LENS) process, possessing Young's modulus (550 GPa), co-efficient of thermal expansion (8.6 × 10−6/K), hardness (396 HV), yield strength in compression (945–1020 MPa), ultimate compressive strength (1020–1096 MPa) and elongation (25–32.5%), thus depicting the microstructure with an excellent interfacial bonding of TiB2 with Ti. A novel optimization algorithm is proposed termed as desirable grey relational analysis (DGRA). Here, the predicted responses obtained from desirability function are further analyzed with the experimental results obtained from wire electro-discharge machining (WEDM), varying power (P), time off (Toff) and peak current (IP), using grey relational analysis. The results are then compared with fuzzy technique for order preference by similarity to ideal solution (FTOPSIS) coupled with fuzzy analytical hierarchy process (FAHP) for criteria weights. Response surface methodology (RSM) is carried on the output performance measures like material removal rate (MRR), surface roughness (SR), kerf width (KW) and over cut (OC), and authenticated by confirmatory tests. Optimized value is improved by 3.09% when compared with desirability to FTOPSIS, 2.05% when evaluated with FTOPSIS to DGRA, and 1.02% when contrasted with desirability to DGRA.